PERANAN MAHKAMAH AGUNG DALAM PENEGAKAN HUKUM DAN KEADILAN MELALUI KEKUASAAN KEHAKIMAN - Rinsofat Naibaho; Indra Jaya M. Hasibuan (Magister Hukum Universitas HKBP Nommensen, 2021)
Judicial power is an independent power to conduct justice and to uphold law and justice. One of the executors of the judicial power was carried out by the Supreme Court. The role of the Supreme Court as the executor of judicial power is urgently needed as a suppressor of any violation of the law, the last place is seeking truth and justice, and the guardian of citizen freedom from all forms of violations of Human Rights. This Research has a formulation of the problem what is the role of the Supreme Court in upholding law and justice and what are the driving factors and obstacles to the Supreme Court in carrying out its role throught the judicial authority. The purpose of this study is to know and understand the extent to which the independence and independence of the Supreme Court at this time, to understand the role of the Supreme Court in upholding law and justice, and to know the driving factors and obstacles of the Supreme Court in carrying out its role through judicial power. Based on the analysis carried out, it was concluded that the Supreme Court in carrying out its duties and functions has 2 (two) roles, that is as the the Supreme Court Judiciary that carries out the judicial function of making regulations to fill the vacancy in order to smooth the judicial process as a State High Institutions that carries out non-judicial functions, which includes providing legal considerations/advice to other State High Institutions.